Eksplanasi Sejarah Dan Implikasinya Dalam Pengembangan Model Pembelajaran SKI Untuk MI - Saidah, Nur (Literasi: Jurnal Ilmu Pendidikan, 2012)
This article describes the explanation of history and its implications in the development of Islamic Culture History learning models in Islamic Primary School. As an independent science, history has a different methodology. Therefore, the explanation is different from the history of other scientific explanations, though conceptually adopted the theory of social and natural sciences to support the explanation. These rules include the historical explanation; regularity, generalization,  statistical inference, periodical, historical narrative and the implications for the development of Islamic Culture History interpretation in Islamic Primary School learning model which requires teachers choose a model student-oriented learning (student centered). For an explanation of the history of the reconstruction of historical events that allow teachers to give crude learning materials so students should be involved to design his own knowledge until he is able to think critically and learn many values from explanation history. One of the today’s appropriate learning models is Contextual Teaching and Learning. This model is a holistic view of learners not only on psychological but also on social and neurotical. This model also requires the integral learning, bringing together the experience of learning in the classroom with daily experiences of students.Keywords: explanation, contextual teaching and learning